2006
DOI: 10.1136/bjo.2006.101170
|View full text |Cite
|
Sign up to set email alerts
|

Central corneal thickness and its relationship to myopia in Chinese adults

Abstract: Aim: To investigate the association between central corneal thickness (CCT) and the degree of myopia among Chinese. Methods: In this prospective observational study, 714 consecutive patients were recruited from a refractive surgery clinic. CCT was measured in both eyes of each patient using the Orbscan (Bausch and Lomb, Rochester, New York, USA), and data of the right eye were selected for analysis. CCT was correlated with the degree of myopia in dioptres (D) using Pearson's correlation coefficient and Dunnett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
41
3
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 17 publications
13
41
3
2
Order By: Relevance
“…Several studies have reported the associations between the refractive error and corneal properties, but are still under debate. 8,9 Chang et al 8 demonstrated an association between the refractive error and corneal dimensions and function in Chinese subjects using the ultrasonic pachymeter. In contrast, Fam et al 9 reported that CCT measured by the Orbscan II pachymeter had no correlation with myopia in Chinese adults.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the associations between the refractive error and corneal properties, but are still under debate. 8,9 Chang et al 8 demonstrated an association between the refractive error and corneal dimensions and function in Chinese subjects using the ultrasonic pachymeter. In contrast, Fam et al 9 reported that CCT measured by the Orbscan II pachymeter had no correlation with myopia in Chinese adults.…”
Section: Introductionmentioning
confidence: 99%
“…may be the main cause of the difference in the biological parameters of the eyes in different regions. [27][28][29] A limitation of our study is that we did not study the corneal thickness of eyes with different diopters or compare eyes between male and female sexes; previous studies have shown that corneal thickness is independent of diopter and sex: there was no significant difference in central corneal thickness between emmetropic and ametropic eyes, 30 among eyes with different diopters, 31,32 or between men and women. 23 Based on these prior research results, we expect that our data should Possessing normal values for corneal thickness-related parameters in the Chinese population will aid in accurate diagnoses of early keratoconus, suspected keratoconus, and other diseases.…”
Section: Discussionmentioning
confidence: 93%
“…This finding agrees with the most of the earlier studies. [12][13][14][15][16][17][18][19][20][21][22] According to such findings, we consider that if the stretching process is actually active, the thinning is likely to be restricted only to the sclera and the cornea is not involved. The current study has the limitation that we measured CCT in the morning and there are studies that investigated the diurnal changes of corneal thickness with various techniques.…”
Section: Cct(micrometer)mentioning
confidence: 99%
“…7 Others have found that CCT is thinner in myopic eyes, [8][9][10][11] while some studies have reported no association between central corneal thickness and degree of myopia. [12][13][14][15][16][17][18][19][20][21][22] The results of this study will help the refractive surgeons how to evaluate and choose the type of the refractive surgeries like the laser in situ keratomileusis and photorefractive keratectomy for myopic patients and to assess the risk of postoperative complications. The purpose of this study was to determine the correlation between central corneal thickness, axial length and myopia.…”
Section: Introductionmentioning
confidence: 99%